Law for business students - Adams, Alix. (Pearson Education, 2012)
Law for Business Students provides an approachable introduction to the law for those new to the subject or studying law as part of a non-law degree. Alix Adams' writing style brings the subject to life and encourages you to apply the law to your experiences and the world around you.